2013
DOI: 10.1088/0952-4746/33/4/773
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception, trust, and factors related to a planned new nuclear power plant in Taiwan after the 2011 Fukushima disaster

Abstract: After the Fukushima nuclear disaster in March 2011, an international review of nuclear safety indicated that two of the three nuclear power plants (NPPs) operating in Taiwan were listed as the most dangerous in the world. To understand the perception of NPP risks by the public in Taiwan and their attitudes regarding a planned fourth NPP after the Fukushima nuclear incident in 2011, a study was conducted in August 2011. A sample of 2819 individuals responded to the survey, with 66% perceiving that Taiwan's safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Visschers and Siegrist [38] show that perceived risks, rather than perceived benefits, before and after the Fukushima nuclear accident, have a negative impact on the acceptability of nuclear energy. Ho et al [49] show that nuclear risk perception is an important determinant in the planning of new nuclear power plants. According to Yamamura [19], perceived risks from nuclear accidents are positively related to experience with technical disasters.…”
Section: Perception Factorsmentioning
confidence: 99%
“…Visschers and Siegrist [38] show that perceived risks, rather than perceived benefits, before and after the Fukushima nuclear accident, have a negative impact on the acceptability of nuclear energy. Ho et al [49] show that nuclear risk perception is an important determinant in the planning of new nuclear power plants. According to Yamamura [19], perceived risks from nuclear accidents are positively related to experience with technical disasters.…”
Section: Perception Factorsmentioning
confidence: 99%
“…Also, increasing concerns about potential nuclear accidents has reduced the support for nuclear energy in many other countries including America, Japan, Switzerland, UK and Taiwan since the Fukushima nuclear accident occurred in 2011 (Hixson, 2012;Ho et al, 2013;Ieong et al, 2014;Keller et al, 2012;World Nuclear News, 2012).…”
Section: Existing Studies On Nuclear-related Risk Perceptionmentioning
confidence: 99%
“…It indicated that the public poses concerns about nuclear power in Taiwan 2 years after Fukushima nuclear disaster. With an increasing anti-nuclear movement in progress, an expectance on the termination of operation of the planned 4th NPP has been ongoing to be discussed after Fukushima nuclear accident (Ho et al, 2013). It showed that trust was the key determinant of the acceptance of a new nuclear power plant and a very small proportion (17%) of respondents in Taiwan trusted the Government's nuclear safety management after Fukushima accident.…”
Section: Potential High Risk Of Nuclear Safety In Taiwanmentioning
confidence: 99%
“…A number of studies were conducted to investigate public risk perception after the Fukushima accident in Japan and its neighboring countries such as Taiwan, South Korea and China [1][2][3][4][5][6][7].…”
mentioning
confidence: 99%
“…while the general public in Taiwan and South Korea were concerned more about the safety of nuclear operation, potential large-scaled harm to the public, and other negative social consequences associated with nuclear accidents [3][4][5][6]. Most importantly, these studies showed a reverse association between risk perception and the public acceptance for nuclear facilities.…”
mentioning
confidence: 99%